ANALISIS PERBANDINGAN PENDAPATAN PETANI PADI SAWAH MELALUI PENGGUNAAN ALSINTAN PASCA PANEN DI KECAMATAN TEBING TINGGI - Putri Narsi; Rahmat Suryanto Pirngadi (Fakultas Pertanian, Universitas Janabadra, 2024)
The average Indonesian farmer is still in the process of applying mechanization to adopt modern and environmentally friendly technology to assist them in agricultural activities. The number of agricultural tools and machinery before and after the harvest period continues to increase, allowing to facilitate farming activities in post-harvest activities and increase production yields. At this time, farmers in Tebing Tinggi sub-district have used two types of machines in post-harvest activities of paddy rice, including using combine Harvester machines and power Thresher machines. The purpose of this research is to analyze how much the comparison of the income of wet-rice farmers through the use of ALSINTAN (Agricultural Machine Tools) post-harvest combine Harvester and power Thresher in Tebing Tinggi sub-district. From the results of this study it was found that farmers who used combine Harvester machines earned an income of IDR 31,561,000 /ha/growing season, while farmers who used power Thresher machines earned an income of IDR 26,377,000 /ha/growing season. Can be concluded that, the income received by farmers using the combine Harvester machine is much more when compared to the income of farmers who use power Thresher machines on wet rice farming activities in Tebing Tinggi sub-district, Serdang Bedagai district, North Sumatra province, with a difference in income of IDR 5,184,000 /ha/growing season. Keywords : analysis, income, rice paddy farmers, power thresher, combine harvester